Microwave remote sensing of the 2011 Plinian eruption of the Grímsvötn Icelandic volcano - MARZANO, FRANK SILVIO; MONTOPOLI, MARIO; Mirko Lamantea; Michael Herzog; Hans Graf; Domenico Cimini (Remote Sensing of Environment, 2013)
The sub-glacial Plinian explosive eruption of the Grímsvötn volcano, which occurred on May 2011, is for the first time analyzed and quantitatively interpreted by using ground-based weather radar data and the Volcanic Ash Radar Retrieval (VARR) physically-based technique. The prevailing southerly winds stretched the erupted plume toward the Artic pole, thus preventing the ash cloud to move toward continental Europe and threatening the airline traffic (different from the less explosive Eyjafjöll eruption on April and May 2010). The 2011 Grímsvötn eruption has been continuously monitored by the Keflavík C-band weather radar, located at a distance of about 260km from the volcano vent. The VARR methodology is summarized and applied to available radar time series to estimate the coarse ash particle category, volume, fallout, concentration and the plume maximum height, every 5min within the volcano vent surroundings (i.e. an area of about 100×100km2 around the volcano). Due to the large distance from the volcano, fine-grained ash cannot be detected and estimated by the Keflavík C-band weather radar. Estimates of the eruption discharge rate, based on the retrieved ash plume top height, are provided together with an evaluation of the total erupted mass and volume. Deposited ash at ground is also retrieved from radar data by empirically reconstructing the vertical profile of radar reflectivity and estimating the near-surface ash fallout. Radar-based ash retrieval results can be compared with available satellite microwave radiometric imagery in order to show the potential contribution and limitations of these microwave remote sensing products to the understanding and modeling of explosive volcanic ash eruptions. Spaceborne microwave brightness temperatures show a correlation with ash columnar content, derived from VARR, depending on the millimeter-wave frequency and on the spatial averaging. Microphysical sensitivity of satellite microwave brightness temperatures to plume fine and coarse ash suggests their exploitation in ...